KELEMBAGAAN LOKAL MINI PURSE SEINE DALAM PENANGKAPAN IKAN DI PERAIRAN SELAT BUTON KECAMATAN DURUKA KABUPATEN MUNA - La Boi; Yani Taufik; Laode Geo (Jurnal Sosio Agribisnis, 2018)
The local institution of mini purse seine is a rule in the mini purse seine group that regulates the cooperation between skipper and labor in catching fish in the waters of Buton strait. In 2010, the number of mini purse seine in Lagasa Village was 40 units and continued to decrease to 30 units in 2017, the number of mini purse seine 30 units. This happens because the skippers sell their fishing gear to the other party as they do not have labors that do fishing. This study aimed to assess the capacity and role of local mini purse seine institutions in fishing in Buton strait waters, Duruka district, Muna Regency. The method of analysis used in this study is descriptive qualitative analysis with the skippers and labors of mini purse seine as the main informant. The results showed that the institutional capacity affecting the sustainability of mini purse seine fishing equipment is the presence of labor. The lack of labor in mini purse seine is caused by low catches, autocratic and symbolic leadership style of the skipper, and violation of the rule of catch fish. The institutional group of mini purse seine has a role in forming cooperative groups in fishing, establishing fishing business units, and advising Lagga Village Government in solving fishing problems in Buton strait waters. Recommendations: The government of Muna regency and its associated elements should increase the institutional capacity of mini purse seine through the strengthening of mini purse seine organizations, institutionalization of values or norms, and resource management.Keywords: Mini Purse Seine; local institution; Bajo Tribe